Pengaruh Person-Organization Fit dan Kepuasan Kerja terhadap Turnover Intention dengan Budaya Organisasi sebagai Variabel Moderasi - Pawestri , Diah Ayu; Dewi, Yustina Erti Pravitasmara (Jurnal Samudra Ekonomi dan Bisnis, 2023)
Organizational effectiveness is not only supported by the success of employees' work tasks, but companies need to pay attention to the behavior of their employees broadly. This is done to minimize the desire of employees to change jobs. The purpose of this study was to determine the effect of person-organization fit and job satisfaction on turnover intention with organizational culture as a moderating variable. Primary data was collected through a questionnaire in which the respondents were 96 people. This explanatory research uses validity test, reliability test, multiple linear regression analysis, path analysis, and sobel test. The empirical results obtained show that partially, both person-organization fit, job satisfaction and organizational culture have a significant effect on turnover intention. Other results show that organizational culture is proven to be a moderation in the influence of person-organization fit and job satisfaction on turnover intention.